Perbandingan Makna Pada Peribahasa Yang Menggunakan Kata “Hati” Dalam Bahasa Mandarin Dan Bahasa Indonesia - Sinar Anwar; Silviani Silviani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Language is unique and universal. Unique means that every language has the same characteristics that are owned by every language in the world and universal means that it has its own characteristics that are not owned by other languages. This study aims to compare the similarities and differences in meaning found in Chinese proverbs and Indonesian proverbs that use the word "heart". Researchers used a qualitative descriptive research design. The data collection technique was carried out using documentation techniques and the data sources for this research were the Xīnhuá chéngyǔ cídiǎn dictionary and the 7700 Indonesian Proverb Dictionary. The results of this study indicate that there are 10 similar meanings in Chinese proverbs and Indonesian proverbs, such as anxiety, honesty, very close relationships and others. Besides that, there are 28 different meanings in Mandarin proverbs and Indonesian proverbs, such as not concentrating, being loyal, being wise and so on. Most describe the state, feelings, behavior and character of a person.